Immune Cells and Molecular Networks in Experimentally Induced Pulpitis. (February 2016) - Renard, E.; Gaudin, A.; Bienvenu, G.; Amiaud, J.; Farges, J.C.; Cuturi, M.C.; Moreau, A.; Alliot-Licht, B.
Dental pulp is a dynamic tissue able to resist external irritation during tooth decay by using immunocompetent cells involved in innate and adaptive responses. To better understand the immune response of pulp toward gram-negative bacteria, we analyzed biological mediators and immunocompetent cells in rat incisor pulp experimentally inflamed by either lipopolysaccharide (LPS) or saline solution (phosphate-buffered saline [PBS]). Untreated teeth were used as control. Expression of pro- and anti-inflammatory cytokines, chemokine ligands, growth factors, and enzymes were evaluated at the transcript level, and the recruitment of the different leukocytes in pulp was measured by fluorescence-activated cell-sorting analysis after 3 h, 9 h, and 3 d post-PBS or post-LPS treatment. After 3 d, injured rat incisors showed pulp wound healing and production of reparative dentin in both LPS and PBS conditions, testifying to the reversible pulpitis status of this model. IL6, IL1-β, TNF-α, CCL2, CXCL1, CXCL2, MMP9, and iNOS gene expression were significantly upregulated after 3 h of LPS stimulation as compared with PBS. The immunoregulatory cytokine IL10 was also upregulated after 3 h, suggesting that LPS stimulates not only inflammation but also immunoregulation. Fluorescence-activated cell-sorting analysis revealed a significant, rapid, and transient increase in leukocyte levels 9 h after PBS and LPS stimulation. The quantity of dendritic cells was significantly upregulated with LPS versus PBS. Interestingly, we identified a myeloid-derived suppressor cell–enriched cell population in noninjured rodent incisor dental pulp. The percentage of this population, known to regulate immune response, was higher 9 h after inflammation triggered with PBS and LPS as compared with the control. Taken together, these data offer a better understanding of the mechanisms involved in the regulation of dental pulp immunity that may be elicited by gram-negative bacteria.